Liking What You See: A Study on the Motives Behind Instagram Likes - Nicholas Valentino Handoko (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
The world has never been more connected than it is today and one key contributor to that fact is the growth of social networking sites. With the sum of about 4.2 billion active users, more than half of the human population, social networking sites have become a highway for information. From holding private conversations to appreciating others’ posts, social media users leave crumbs of information – one of which is a “Like”. ‘Like’ carries a plethora of information, and decoding it offers invaluable insight. This research aims to study the motives behind the act of ‘Liking’ an Instagram post. Following the data collection, an analysis using Albert Bandura’s Social Cognitive Theory will be carried out. With it, the researcher concluded that the motives behind ‘Liking’ an Instagram posts are to manage relationship, form an identity, state affinity, provide support, and prompt similar behavior.Keywords: Social media, Instagram, Instagram Like, Social Cognitive Theory (SCT), Motives